Effect of white popinac (Leucaena latisiliqua) on field crops and nutrient addition in soil under agro-forestry system - PRASAD, ARJUN; PRASAD, S N (The Indian Journal of Agricultural Sciences, 2013)
A field experiment Was conducted during 1983-93 at Kota in Rajasthan to study the compatibility of different field crops with white popinac [Leucaena latisiliqua (L.) Gillis; syn L. leucecophala (Lam.) de Wit] planted 1m apart on 1 side of Held hund in agro-forestry system. Growing of white popinac reduced the yield or all field crops near the vicinity of tree. On an average, sorghum (Sorghum hicolor (L.) Moench] + pigeonpea (Cajanus cajan (L) Millsp] were more compatible with white popinac, giving the maximum sorghum grain-equivalent yield (3 152 kg/ha) than other crops. The reduction in crop yield could be minimized by proper pruning and lopping and can be compensated by standing biomass of trees (fuel wood 238 kg and fodder 68 kg/tree). White papinac increased the soil fertility by adding 34.6 tonnes/ha organic matter (N, P and K 901, 52 and 416 kg/ha respectively) through litter during 10 years.